2018
DOI: 10.1097/md.0000000000009520
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefits of pelvic lymphadenectomy versus pelvic and para-aortic lymphadenectomy in patients with endometrial cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…The SEPAL study also concluded that stage III–IV patients could benefit from the addition of chemotherapy 6. A recent meta-analysis concluded that para-aortic lymphadenectomy up to the renal vein is associated with favorable survival outcome in intermediate- or high-risk patients compared with pelvic lymph node dissection 7. In the present study, no significant effect of para-aortic lymphadenectomy could be found, but both the number of patients (62) and the average number (5,5) of lymph nodes removed were low, indicating insufficient para-aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The SEPAL study also concluded that stage III–IV patients could benefit from the addition of chemotherapy 6. A recent meta-analysis concluded that para-aortic lymphadenectomy up to the renal vein is associated with favorable survival outcome in intermediate- or high-risk patients compared with pelvic lymph node dissection 7. In the present study, no significant effect of para-aortic lymphadenectomy could be found, but both the number of patients (62) and the average number (5,5) of lymph nodes removed were low, indicating insufficient para-aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…11 This result was confirmed by a recent meta-analysis, concluding that para-aortic lymphadenectomy combined with pelvic lymphadenectomy is associated with favorable survival outcomes in patients with endometrial cancer with intermediate or high risk of recurrence compared with pelvic lymphadenectomy alone. 12 Thus, it seems advisable to select only patients at high risk for nodal involvement for complete lymphadenectomy. However, because of the uncertainty of whether and at which stages lymphadenectomy is of therapeutic or diagnostic benefit, extent of lymphadenectomy varies extremely all over the world from no lymphadenectomy at all to resection of all nodes in every patient.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with combined pelvic and para-aortic lymphadenectomy compared to pelvic lymphadenectomy had a better 5-year OS of 85% vs. 76% (relative risk (RR) 1.13, 95% CI 1.04–0.24, I2 = 57.3%). Subgroup analysis in a formerly published meta-analysis indicated that the positive effect of combined pelvic and para-aortic lymphadenectomy could only be detected in intermediate- or high-risk patients [ 28 ]. No significant difference in OS was found in low-risk EC patients, defined as FIGO stage IA, grade 1–2 and endometrioid histology without lymphovascular space invasion (LVSI).…”
Section: Factors Incorporated In Surgical Stagingmentioning
confidence: 99%